Das SARO-Gutachten (1961): Beurteilung von Entstehung, Inhalt und Wirkung - Mäding, Heinrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
The paper provides a historical review and appraisal of the 1961 report by the Expert Committee Responsible for Spatial Planning (SARO), which is judged to have had great significance for the start-up phase of federal spatial planning in Germany. The focus of the analysis is on a detailed evaluation of the text according to five key questions concerning its suitability as a policy advice document. Looking back to the policy advice demands of the time, the extent to which the text fulfilled the task allocated to the committee is assessed. Looking forwards, the political resonance of the text is outlined using important spatial planning documents of the years up to 1975. It is concluded that the suitability of the text for providing policy advice is limited by a number of factors. Criticisms include the use of the carrying capacity concept as a benchmark and the insufficient elaboration of the strategy in both material and procedural terms. Nonetheless, the political resonance of the document was positive and the report represented an important step towards the Spatial Planning Act of 1965.